The Role of Digital Media in Optimizing Project-Based Learning to Practice 21st Century Skills - Sinta, Dewi; Faqihuddin, Achmad; Nurhuda, Abid; Ab Rahman, Engku Shahrulerizal Bin Engku (LPPI Yayasan Almahmudi bin Dahlan, 2024)
The utilization of digital media in learning is crucial in the current era of education, especially in training 21st-century skills. This study explores digital media's role in optimizing project-based learning in an Islamic high school in Indonesia. The selection of this school as the research subject is based on the utilization of digital media in the learning process, which has been carried out regularly, so it is beneficial in optimizing project-based learning. This research uses a qualitative approach with a case study design. Data collection was conducted through observation, interview, and document analysis. Data analysis techniques include reduction, display, verification, and conclusion drawing. The results showed that examples of project-based learning activities in this school include learning to make dioramas from recycled paper, resin bed lamps, generator mock-ups, environmental campaign posters, and plant naming signs. These project-based learning activities are instrumental in training students' 21st-century critical thinking, creativity, digital literacy, collaboration, and problem-solving skills. Digital media in this study acts as an idea generator and inspiration to find much scientific information, not least related to making name signs on a plant. This study indirectly contributes insight into examples of teacher creativity regarding the use of digital media to create interesting and meaningful learning.